Pengaruh Vulva Hygiene Terhadap Pencegahan Risiko Infeksi Luka Ruptur Perineum - busroh, khafiatun; Yuni Purwati (NERSMID : Jurnal Keperawatan dan Kebidanan, 2025)
Vulva hygiene is cleaning the vulva and surrounding area in postpartum maternal patients. Perineal rupture is a laceration that occurs in the genital area (perineum) directly or using a tool. One of the steps that mothers can take is with vulvar hygiene.  The purpose of her research was to be able to manage postpartum nursing care for Mrs. "R" aged 26 years with treatment of perineal wounds of the second degree at PKU Muhammadiyah Hospital Bantul. The method of data collection and collection is carried out directly and thoroughly by including various data sources. The data collection techniques in the case study include interviews, observations and documentation studies which are carried out for 1x24 hours with the provision of interventions for 15 minutes according to the standard operating procedures (SPO) with 3S guidelines (SDKI, SLKI, SIKI). The results of the case study conducted on the evaluation of the patient's perineal care after vulva hygiene for 1x24 hours did not show any infection where the results of REEDA observation on the wound were no redness in the wound, no swelling (edema), no bleeding under the skin (Ecchymosis), no bleeding or pus (Discharge) and good tissue linkage, The stitch wound looks sticky and nice (Aproximation). The conclusion of the case study was that perineal care intervention with vulva hygiene in patients affected the risk of perineal rupture wound infection.